2015
DOI: 10.2298/vsp140109071t
|View full text |Cite
|
Sign up to set email alerts
|

Functional recovery of patients with ischemic cardiomyopathy treated with coronary artery bypass surgery and concomitant intramyocardial bone marrow mononuclear cell implantation: A long term follow-up study

Abstract: Implanatation of BMMNC concomitant to CABG is a safe and feasible procedure that demonstates not only the improved functional capacity but also a reduced cardiac mortality in a 5-year follow-up in patients with ischemic cardiomyopathy scheduled for CABG surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 21 publications
0
22
0
4
Order By: Relevance
“…In addition, the mean and SD of the LVEF BMSC change and LVEF control change were not directly reported by certain studies (3,5,6,9,10,12,13,15,16). The mean of the LVEF BMSC change and LVEF control change may be easily obtained by calculating the difference between the means of the LVEF baseline and LVEF follow-up .…”
Section: Methodsmentioning
confidence: 96%
“…In addition, the mean and SD of the LVEF BMSC change and LVEF control change were not directly reported by certain studies (3,5,6,9,10,12,13,15,16). The mean of the LVEF BMSC change and LVEF control change may be easily obtained by calculating the difference between the means of the LVEF baseline and LVEF follow-up .…”
Section: Methodsmentioning
confidence: 96%
“… 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 Furthermore, intramyocardial injection of investigational medicinal products during coronary artery bypass grafting had a similar safety profile to surgery alone in seven published studies. 9 , 10 , 11 , 12 , 13 , 14 , 15 The choice of a short narrow-gauge needle for intramyocardial injections in the present study minimizes the risks of perforation and bleeding at the injection site.…”
Section: Main Textmentioning
confidence: 99%
“… 7 , 8 Clinical trials have, however, demonstrated the safety of epicardial injections in patients undergoing coronary artery bypass grafting. 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 Lack of efficacy may result from poor gene transfer efficiency, poor expression levels, low bioactivity of the expressed protein, suboptimal pharmacokinetics with constitutive promoters, and inaccurate targeting of ischemic but viable myocardium. 17 …”
Section: Main Textmentioning
confidence: 99%
“…The object of our recent study (39) was to test the hypothesis that intramyocardial MNC/SC implantation associated with CABG surgery leads to better postoperative results than CABG surgery alone -regarding the "primary-end-point": patients functional capacity and the "secondary-end-point": cardiovascular mortality in the follow-up period of 5 years. Six minute walk test (6-MWT) was used to evaluate patient's functional capacity.…”
Section: Stem Cells For Cardiac Repairmentioning
confidence: 99%